PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KUALITAS PENDIDIKAN: A SYSTEMATIC LITERATURE RIVIEW - Syahrulyadi, Muhammad; Jungso, Amir; Darmayanti, Mela; Nurhayati; Basir, Sutrisman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Training and development are two important topics when discussing the human resources of an institution, company or organization. The aim of this research is to explore the importance of training and human resource development in improving the quality of education. This article will also discuss several important things related to training and human resource development in the education sector. It is hoped that this article can provide useful insights and recommendations for the government, educational institutions and educational practitioners in efforts to improve the quality of education through training and human resource development. This research used the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analysis) method which was carried out systematically according to predetermined stages or protocols. A systematic review is a research method that aims to evaluate, identify and analyze all previous research findings related to a particular topic, study or phenomenon of current concern. The conclusion of this research is that through training and human resource development, teachers can develop their expertise in the best teaching methods, so they can provide quality education to students.